2021
DOI: 10.1021/acs.orglett.1c00938
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Complex Cyclobutane Building Blocks by Photosensitized [2 + 2] Cycloaddition of Vinyl Boronate Esters

Abstract: Cyclobutyl moieties in drug molecules are rare, and in general, they are minimally substituted and stereochemically simple. Methods to assemble structurally complex cyclobutane building blocks suitable for rapid diversification are thus highly desirable. We report herein a photosensitized [2 + 2] cycloaddition with vinyl boronate esters affording straightforward access to complex, densely functionalized cyclobutane scaffolds. Mechanistic studies suggest an activation mode involving energy transfer to the styre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 62 publications
0
37
0
Order By: Relevance
“…In order to improve the reaction yield, two different approaches were then envisaged. In the first approach, we were inspired by the pioneering studies of Lewis on Lewis‐acid complexes in photochemical reactions, [15] as well as similar studies by Yoon and co‐workers, Bach and co‐workers, and many others [7j,16] . We questioned whether a similar phenomenon can be employed utilizing a Brønsted acid (protonation).…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve the reaction yield, two different approaches were then envisaged. In the first approach, we were inspired by the pioneering studies of Lewis on Lewis‐acid complexes in photochemical reactions, [15] as well as similar studies by Yoon and co‐workers, Bach and co‐workers, and many others [7j,16] . We questioned whether a similar phenomenon can be employed utilizing a Brønsted acid (protonation).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting crude was purified by chromatography on silica gel ( n -hexanes/EtOAc, under gradient) affording product 1u as a yellow oil (532 mg, 53%). The spectral data for this compound correspond to the literature …”
Section: Methodsmentioning
confidence: 99%
“…It is pertinent to note this allowed a series of boron functionalities of different hybridisation states to be compatible with model reaction conditions. Recently Brown and co‐workers provided a striking example demonstrating EnT‐catalysed intermolecular [2+2] cycloaddition of alkenyl boronic esters (Scheme 18, bottom) [103] . Mechanistic studies identified a triplet energy transfer mechanism highlighting that energy is transferred to the alkenyl (styrene or diene) organoboron species.…”
Section: Photochemical Strategies Retaining the C−b Bondmentioning
confidence: 99%